2021
DOI: 10.3390/plants10050973
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs for Spot Blotch Resistance in Two Bi-Parental Mapping Populations of Wheat

Abstract: Spot blotch (SB) disease caused by the hemibiotrophic pathogen Bipolaris sorokiniana inflicting major losses to the wheat grown in warm and highly humid areas of the Indian subcontinent, including Bangladesh, necessitates identification of QTLs stably expressing in Indian subcontinent conditions. Thus, two RIL mapping populations, i.e., WC (WUYA × CIANO T79) and KC (KATH × CIANO T79), were phenotyped at Dinajpur, Bangladesh for three consecutive years (2013–2015) and genotyped on a DArTseq genotyping by sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
(96 reference statements)
1
11
0
Order By: Relevance
“…On chromosome 2AS, the markers in the region between 718152 and 24002740 bps were in the same position as a previously reported spot blotch associated marker S2A_16824871 (Jamil et al, 2018) and QTL (Gahtyari et al, 2021), besides the 2NS translocation from Aegilops ventricosa (Juliana et al, 2019(Juliana et al, , 2020aGao et al, 2021). This is a key finding in this study, which is the first report of the association of the 2NS translocation with spot blotch resistance.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…On chromosome 2AS, the markers in the region between 718152 and 24002740 bps were in the same position as a previously reported spot blotch associated marker S2A_16824871 (Jamil et al, 2018) and QTL (Gahtyari et al, 2021), besides the 2NS translocation from Aegilops ventricosa (Juliana et al, 2019(Juliana et al, , 2020aGao et al, 2021). This is a key finding in this study, which is the first report of the association of the 2NS translocation with spot blotch resistance.…”
Section: Discussionsupporting
confidence: 87%
“…On chromosome 1AL, we observed that significant marker 1A_579403901 was 2.9 Mbps away from spot blotch associated marker S1A_582293281 ( Jamil et al, 2018 ), and might be possibly indicating it or a novel locus. On chromosome 1BL, considering the marker 1B_673569173 that was significant in three panels, we observed that it was: (i) 4.7 Mbps away from marker hbe248 that was linked to the Lr46/Sr58/Yr29/Pm39/Ltn2 locus and tagged a minor spot blotch QTL ( Lillemo et al, 2013 ), (ii) in the same position as a spot blotch associated region reported by Gahtyari et al (2021) between 670.6–673.7 Mbps and (iii) 0.78 Mbps away from marker IWB5678 that was distal to the Lr46/Sr58/Yr29/Pm39/Ltn2 locus ( Singh et al, 1998b ; Kolmer et al, 2019 ). This indicates that marker 1B_673569173 and the other markers in the LD block are closely linked to the Lr46/Sr58/Yr29/Pm39/Ltn2 locus, thereby providing further evidence to the association of this locus with spot blotch resistance, in addition to partial and durable resistance to rust diseases and powdery mildew ( Lillemo et al, 2013 ).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The full-sibs populations used in this study included Bartai × Ciano T79 (BC), Cascabel × Ciano T79 (CC), Kath × Ciano T79 (KC) and Wuya × Ciano T79 (WC) (Singh et al 2018a ; He et al 2020 ; Gahtyari et al 2021 ; Roy et al 2021 ). Each of them comprised 231 progenies, obtained from crossing a susceptible cultivar Ciano T79 (BUCKY/(SIB)MAYA-74/4/BLUEBIRD//HD-832.5.5/OLESEN/3/CIANO-67/PENJAMO-62) with four resistant cultivars including: (1) Bartai (BABAX/LR42//BABAX/3/ERA F2000) (2) Casacabel (SOKOLL//W15.92/WEEBILL1) (3) Kath (WHEATEAR/KRONSTAD F2004) and (4) Wuya (WAXWING*2/CIRCUS).…”
Section: Methodsmentioning
confidence: 99%
“…Evaluations of spot blotch in the KC and WC populations in Dinajpur and the CC population in Varanasi are described in Gahtyari et al ( 2021 ) and Roy et al ( 2021 ), respectively. For all the populations, the percentage disease severity and the relative area under the disease progress curve (rAUDPC) (Simko and Piepho 2012 ) values, where the AUDPC was expressed relative to the most susceptible line (whose rAUDPC was assumed to be 100) were obtained from the double-digit scores.…”
Section: Methodsmentioning
confidence: 99%